TANGGUNGJAWAB KORPORASI DALAM TINDAK PIDANA KORUPSI PADA PT ASURANSI JIWASRAYA (PESERO)(Analisa Putusan Nomor 30/Pid.Sus/Tpk/2020/PN.Jkt.Pst) - Desi Desturi (2021)
A corporation is an entity or legal subject whose existence makes a major contribution in increasing economic growth and national development, but in reality, corporations sometimes also commit various criminal acts (corporate crimes) that have a detrimental impact on the state and society. A corporation can be considered to have committed a crime based on the actions of a person who controls the management of the corporation. PT. Asuransi Jiwasraya (Company) as a state-owned company in recent years has been in the spotlight. PT. Asuransi Jiwasraya (Government company) is unable to fulfill its customer's maturity policy obligations of around Rp 12.4 trillion. The default of PT. Asuransi Jiwasraya (Government company) actually occurred in one of its flagship products, the JS Saving plan. JS Saving plan is a life insurance product as well as an investment offered through banking or bancassurance. In contrast to unit-linked insurance products where the investment risk is borne by the policyholder, the JS Saving plan is a non-unit-linked investment whose risks are fully borne by the insurance company. The purpose of this study was to determine the implementation of corporate responsibility in the case of PT. Asuransi Jiwasraya (Government company) and to determine the optimization of corporate responsibility for the perpetrators of corruption at PT. Asuransi Jiwasraya (Government company) in returning losses to the state and customers (the public). The type of research used in writing this thesis is a normative legal research type. The results obtained are that in the corruption case that occurred at PT. Asuransi Jiwasraya (Government company) there were several perpetrators who were charged, one of which was Heru Hidayat who is the main commissioner of PT Trada Alam Minera who also manages and controls corporations involved in criminal acts. Corruption Deviations in Financial Management and Investment Funds by PT. Asuransi Jiwasraya (Government company). Heru Hidayat as one of the main actors in the corruption case has now been sentenced to life imprisonment plus a replacement money of Rp 10.73 trillion. Meanwhile, the corporations that have been accused are 13 Investment Manager Companies which have been transferred to the Corruption Court at the Central Jakarta District Court and are currently in the trial process.